Effects of increased training volume during a ten-day training camp on competitive performance in national level youth swimmers - Nugent, F. J.; Comyns, T. M.; Warrington, G. D. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The purpose of this study was to investigate the effects of increased training volume during a 10-day training camp on competitive performance and internal training load (ITL). In addition, coach and swimmer rating of perceived exertion (RPE) for each session was compared. METHODS: Ten national level swimmers (gender: 4 males and 6 females; age: 15±1 years; height: 170.5±6.4 cm; body mass: 61.4±7.4 kg) participated in the training camp which involved a 36% increase in swimming volume. Competitive performance, as assessed using the FPS (FINA points system), was recorded pre and post-camp. ITL was recorded using the Session-RPE method and RESTQ-52 Sport questionnaire for each session and for day 1, 5 and 10 of the camp, respectively. Coach RPE was recorded after each training session for coach-swimmer RPE comparisons. RESULTS: Competitive performance increased by 7.1% from pre-camp to post-camp (P=0.001, dz=1.6). Session-RPE increased between day 1 and all other days of the training camp (P<0.05), except day 6 (P=0.221). The injury scale of the RESTQ questionnaire increased from day 1 to day 5 (P=0.022). Across 16 swimming sessions, there was a strong correlation between coach and swimmer RPE (rs=0.76) however RPE was found to be higher for the swimmers than the coach (P=0.0005) during moderate training sessions. CONCLUSIONS: These findings suggest that a 36% increase in swimming volume during a 10 day training camp resulted in significant changes to competitive performance and ITL. However, coach and swimmer RPE should be monitored closely during future camps.